SIKAP MASYARAKAT NELAYAN TERHADAP PELARANGAN ALAT TANGKAP DOGOL (Danish seines) DI DESA MUARA TELAKE KECAMATAN LONG KALI KABUPATEN PASER - Abdul Wahid; Gusti Haqiqiansyah; Dayang Diah Fidhiani (2339-1324, 2019)
The aimed of the research was to find out the process of disseminating the Dogol fishing gear prohibition policy and assessing the attitudes of fishermen to the prohibition of Dogol fishing gear in Muara Telake Village. The research was held on September 2018 until October 2018. The location of this research was in Muara Telake Village, Long Kali Sub-District, Paser Regency. Sampling used purposive sampling method and Slovin formula. The method of data analysis was descriptive analysis to determined the process of socializing the policy of prohibiting Dogol fishing equipment and Likert scale analysis to assessed the attitude of fishermen to the prohibition of Dogol fishing gear. The results of the research showed that the socialization activities from the government obtained a negative result because fishermen rejected the Dogol fishing gear prohibition policy and the attitudes of fishermen in Muara Telake Village accumulatively was at a moderate level with a value of 16.08, which means that the fishermen hesistan about regulation. The attitudes of fishermen based on cognitive attitude indicators in the high category with a value of 7.45, which means that fishermen had knowledge, affective and conative indicators were in the low category with a value of 4.53 and 4.10, which meansthat the fishermen rejected the policy and did not intend to replace fishing gear.